L’acceptabilité sociale, les décideurs publics et l’environnement - Corinne Gendron; Stéphanie Yates; Bernard Motulsky (VertigO)
In a context where representative democracy is opening up to participative democracy, public decision-makers are nowadays encouraged to consult civil society actors and to justify their decisions to them, notably in relation to large-scale projects that raise environmental concerns. This dynamic poses several challenges to executive sphere’s actors. Thus, if the principle of participative democracy is generally admitted, its concrete and practical implications still have to be understood, as well as its articulation with representativeness and deliberation, two other principles underlying the construction of public decision-makers’ legitimacy. In light of the Quartier des Spectacles project, recently discussed in Montreal (Quebec), we show how the contested nature of social acceptability and of the notion of participative democracy in itself leaves some flexibility to actors from the executive sphere. If participatory approach’s benefits are gradually recognized, at least in some contexts, the case shows that the ways it can take place as a complement to representative democracy are still debated. As a result, actors from the executive sphere can suddenly decide to shut the doors of the participation path.